Marketing Apparel and Footwear - Moschis G.P. (2023)
This chapter consists of three main sections. The first section presents information on the needs of older consumers that tend to emerge due to aging. It focuses on factors that create needs for specific apparel attributes that manufacturers should consider in developing product lines for the aging population. The second section presents research on older consumers’ buying and consumption habits regarding apparel products. The information presented in the first two sections has implications for designing effectual strategies and tactics for marketing apparel and footwear products. The last section of the chapter uses information presented in the chapter’s earlier sections and earlier chapters in this book to suggest strategies for marketers of apparel and footwear products. It offers recommendation for marketing strategies (segmentation, target selection and positioning), programs and tactics (product development, promotion, pricing and distribution) for manufacturers and retailers of apparel and footwear.